CULTURAL AND ECONOMIC RELATIONS BETWEEN UZBEKISTAN AND EGYPT HISTORY - F. Erimmatova; G.A Erimmatova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: In this article, the development of multilateral and mutually beneficial relations with Arab countries, in particular with the Arab Republic of Egypt, is one of the priorities of Uzbekistan's foreign policy, and in particular, cooperation in the educational and economic spheres is the basis of mutual rapprochement. shown.